Ichthyofauna of the Diamante stream, Caiuá Ecological Station (Diamante do Norte, Paraná State): monitoring its composition and structure - DOI: 10.4025/actascibiolsci.v31i2.3907 - Morales, Bruno Ferezim (2009)
The aim of this study was to assess of composition and structure of ichthyofauna over two distinct periods: three and eleven years after the establishment of the protected area. The results of composition and structure of the ichthyofauna of the Diamante River, sampled quarterly from November 2005 to August 2006, were compared to results obtained by Abilhoa and Bastos (2005) in studies conducted between August 1997 and December 1998. The 2.4 to 16 cm-mesh gillnets were exposed for 24 hours and checked every 8 hours. In order to characterize the ichthyofauna, patterns of species richness, diversity, evenness and frequency of occurrence of species were analyzed. A total of 673 individuals, distributed among 36 species, 13 families and four orders were sampled. Significant changes were found in ichthyofauna composition, with a reduction in diversity and evenness as compared to the previous study. The high representativeness of alien species indicates instability in the studied area, through changes in diversity, species replacement, predominance of opportunistic species, and physical changes such as silting and degradation of the body of water.